Aspek biologi dan dinamika populasi ikan tenggiri (Scomberomorus commerson Lacepede 1800) di Perairan Arafura - Andina Ramadhan Putri Pane; Siti Mardlijah; Budi Nugraha; Ali Suman (Depik Jurnal, 2020)
Abstract. The Arafura waters are rich in fishery resources such as shrimp, demersal fish, pelagic fish, and crustaceans. The Tenggiri fish (Scomberomorus commerson) is the mainstay of pelagic fisheries and is dominant landed in 2 (two) locations in Poumako (Mimika) and Dobo (Aru Islands). The number of samples measured during the study was 2,645 species derived from the waters of Arafura. The production of fisheries increased to be an indication that it is necessary to manage the intensive utilization of fish resources to keep the population. Management requires basic scientific study of biological aspects and population dynamics of Narrow-bareed mackerel. The study was conducted from March to December 2017 in Poumako and Dobo. The 35-130 cmFL fish size structure is dominant at a size of 95 cmFL with negative allometric growth. The length at the first catch is 78 cmFL with a growth rate of (K) = 0.86 per year and an infinitive length (L∞) = 136.5 cmFL. Fish were first to catch at the age of 10 months, and the age reached infinitive (L∞) is 9.5 years old. The recruitment of the fish from August (11.82%) up to October (18.13%) with a peak of September at 23.75%. The fishing mortality (F) is higher than that of natural mortality (M) so that the exploitation rate (F) = 0.67, which indicates that overfishing has occurred in this area. One form of fisheries management that can be done is to limit the fishing season to provide the opportunity of fish to reproduce and recruitment to restore the population.